2016
DOI: 10.1016/j.jebo.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of corporate social responsibility through charitable giving in Bertrand markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…This result agrees with the findings of social exchange theory which refers that employees can perceive and understand the benefits they gain through CSEV. Therefore, they reciprocate these positive attitudes with their company in the form of most environmental engagement by affective committing towards CSR programmes (Sanchez‐Hernandez and Gallardo‐Vázquez, ; Kaur, ; Megan and Maryam, ; Alhouti et al ., ; Feicht et al ., ; Breitsohl and Ehrig, ; Haleem et al ., ). Additionally, the results showed that CSEV in environmental corporate strategy was particularly crucial in establishing an organizational link between the external and internal dimensions of CSR.…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the findings of social exchange theory which refers that employees can perceive and understand the benefits they gain through CSEV. Therefore, they reciprocate these positive attitudes with their company in the form of most environmental engagement by affective committing towards CSR programmes (Sanchez‐Hernandez and Gallardo‐Vázquez, ; Kaur, ; Megan and Maryam, ; Alhouti et al ., ; Feicht et al ., ; Breitsohl and Ehrig, ; Haleem et al ., ). Additionally, the results showed that CSEV in environmental corporate strategy was particularly crucial in establishing an organizational link between the external and internal dimensions of CSR.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the markets for fair trade and organic products flourish. Experimental evidence confirms that consumers positively respond to a firm's ethical conduct (e.g., Danz et al, 2012;Feicht et al, 2016, andPigors andRockenbach, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Related experiments that also use a market framing (Bartling and Weber, 2013;Rode et al, 2008;Etilé and Teyssier, 2012;Feicht et al, 2014) have shown that subjects' allocation behavior is not as extreme as expected under common knowledge of selfish preferences and that deviations may be explained by social preferences. The next section will discuss the predictions of prominent social preference theories for our setups.…”
Section: Hypothesis 1: Selfish Preferencesmentioning
confidence: 99%
“…Its 5 degree is experimenter imposed and randomly attached to one of the three producers. This problem is partially solved by Etilé and Teyssier (2012) as well as Feicht, Grimm, and Seebauer (2014) by endogenizing the level of the donation to an NGO. The treatments vary the credibility of signals on donations.…”
Section: Related Literaturementioning
confidence: 99%